Pengembangan Karakter Berlandaskan Nilai Pancasila Melalui Pendidikan Pancasila pada Program Studi Elektro - Valentinus Fabriananto; Rimathul Hanifah; Agus Kumalasari; Hendy Marzelly; Khanifatunnisa; Zulfi Chumaidi; Muhammad Hamim Fithrony; Suyono Suyono (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study examines the role of Pancasila education in teaching Pancasila values to build student character. As the basic ideology of Indonesia, Pancasila provides principles and guidelines emphasizing the value of faith in God, humanity, unity, democracy, and social justice. These values are very important in creating student graduates who excel academically and have integrity according to the character of the Indonesian nation. Therefore, this study aims to explore the effectiveness of Pancasila education in building a good and relevant character in students of the Electrical Study Program. The method used in this research approach is qualitative descriptive with data-based literature and analysis, document analysis, and observation on students of related study programs. The data that has been found shows that Pancasila education can increase students' awareness of the noble values of Pancasila such as cooperation, justice, and social responsibility. Another finding in the research is that Pancasila education can foster a sense of nationalism and empathy for students in daily life. This study concludes the role of Pancasila education as a strategic effort in forming a moral and socially responsible generation. Therefore, higher education is advised to strengthen the teaching of Pancasila values through Pancasila education with an innovative approach according to student needs.